(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The existing water is becoming polluted nowadays due to high anthropogenic emission of water. The phytoremediation technology is used to treat the contaminated soil and water which containing higher amount of pollutants. The water that contains heavy metals will cause water scarcity and affect on human health when human drink the water. In this study, Colocasia esculenta was chosen for the removal of Cr(VI) in water. The efficiency of C.esculenta in accumulates Cr(VI) in synthetic wastewater was evaluated. The effect of time and concentration of Cr(VI) were identified in this study. Cr(VI) concentration was determined using diphenylcarbazide method (DPC). Experiment were set up in Laboratory Scale Constructed Wetlands with varies the concentration of synthetic wastewater of 1, 2, 5, 10, 50, 500 and 1000 mg/L and was continued for 36 days. The result of removal percentage for the 1, 2, 5 and 10 mg/L reach 100% while for 50, 500 and 1000 mg/L only remove 99.99%, 94.79% and 55.84% respectively. Roots of C.esculenta are able to accumulate Cr(VI) in wastewater which with BCF value was 1.557 mg/L. The BCF value of roots were more than 1, represents the higher accumulation of metal in plant. Therefore, C.esculenta has potential to use in removing Cr(VI) in water.